2017
DOI: 10.4317/jced.53816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of shear Bond Strength of universal Dental Adhesives -An in vitro study

Abstract: BackgroundPatient demand for tooth colored restorations and desire for minimally invasive restorations have made composites an indispensable part of the restorative process. An important factor affecting the intra-oral performance of composite restorations is bonding.Material and MethodsNinty six freshly extracted molar teeth were collected and occlusal 3mm is removed using a diamond disc to expose dentine. Following with samples were divided in to two main groups (self-etch & total etch). Each main group is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 6 publications
2
38
1
2
Order By: Relevance
“…Shear bond strength (SBS) is a mechanical test of the adhesive interphase that can provide an indication of the bond integrity between esthetic restorations and dentin surface. Reliable results were achieved in previous researches studying dentin-adhesives interphase (12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Introductionmentioning
confidence: 78%
“…Shear bond strength (SBS) is a mechanical test of the adhesive interphase that can provide an indication of the bond integrity between esthetic restorations and dentin surface. Reliable results were achieved in previous researches studying dentin-adhesives interphase (12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Introductionmentioning
confidence: 78%
“…40,41 Therefore, the presence of MDP in the SBadhesive may underlie the higher associated bond strength. 42 The chemical composition of TNB is based on a combination of hydrophilic hydroxyethyl methacrylate (HEMA), hydrophobic decanediol dimethacrylate (D3MA), intermediate bisphenol A glycidyl methacrylate (bis-GMA)monomers, MDP, and methacrylated carboxylic acid polymer (MCAP). 42 This combination of properties permits the TNB adhesive to dependably bridge the gap between the hydrophilic tooth structure and the hydrophobic restorative resin material under various surface conditions.…”
Section: Discussionmentioning
confidence: 99%
“…42 This combination of properties permits the TNB adhesive to dependably bridge the gap between the hydrophilic tooth structure and the hydrophobic restorative resin material under various surface conditions. 42 Moreover, both universal adhesives showed better bond strengths when the enamel surface was pre-treated with phosphoric acid. This finding agrees with the findings of many previous studies showing that applying acid etch in conjunction with SE adhesive systems, mainly in the enamel, is important.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding shear bond strength, results have demonstrated that Clearfil self-etch adhesive has superior bond strengths compared with Universal adhesives. 31 The results of studies show that substrate type is one of the factors that affect adhesive bonding. 32 In fact, the chemical properties of a substrate, which may be dental tissue or restorative materials, has an effect on the type of adhesive applied and the amount of strength it produces.…”
Section: Discussionmentioning
confidence: 99%